2024
DOI: 10.1039/d3ta06383f
|View full text |Cite
|
Sign up to set email alerts
|

Defect dipoles and stable dielectric properties improve Nb-doped Ba0.7Sr0.3TiO3 photocatalytic H2 evolution activity

Kefan Liu,
Zhaoyu Wang,
Guanqi Wang
et al.

Abstract: To enhance the photocatalytic hydrogen evolution reaction (HER) activity and stability of barium strontium titanate (Ba0.7Sr0.3TiO3, BST), niobium (Nb5+) donor doped BST (Ba0.7Sr0.3Ti1-xNbxO3) photocatalysts were synthesized via the sol gel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…13 So far, BTO is utilized primarily for the HER in the presence of external bias and ultraviolet light as the photon source. 14,15 However, the valence band of BTO is situated at a potential sufficiently high to facilitate the oxidation of water and the generation of oxygen. 16 Therefore, this material holds promise as an OER photocatalyst for producing oxygen concurrently with hydrogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 So far, BTO is utilized primarily for the HER in the presence of external bias and ultraviolet light as the photon source. 14,15 However, the valence band of BTO is situated at a potential sufficiently high to facilitate the oxidation of water and the generation of oxygen. 16 Therefore, this material holds promise as an OER photocatalyst for producing oxygen concurrently with hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…21 As a photocatalyst for water-splitting, BTO has a significant drawback of rapid electron–hole recombination during photocatalytic reactions. 22 To address the challenges outlined and design an effective photocatalyst for the process of photocatalytic water-splitting, it is necessary to reduce the band gap energy of BTO while preserving its inherent ferroelectric properties so that its polarization can contribute to charge separation during reactions. It is reported that the Jahn–Teller charge neutral dipole doping strategy can achieve lower band gap energy and at the same time it can retain its spontaneous ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%